A statistical damage constitutive model based on unified strength theory for embankment rocks. Issue 7 (8th August 2020) - Shen, Peiwu; Tang, Huiming; Wang, Dingjian; Ning, Yibing; Zhang, Yongquan; Su, Xuexue
Abstract: Fluctuant marine and reservoir water levels are the main failure-inducing factors for embankment slopes. The soft embankment rocks, e.g., red-bed mudstone, eroded by the reservoir water level in the Three Gorges Reservoir area greatly influence the stability of the embankment slopes. In this study, unified strength theory was innovatively applied for damage evaluation and combined with the Weibull distribution to obtain the strength statistics of micro units. Additionally, one damage constitutive model and one damage evolution model considering the initial damage, strain softening and damage weakening were proposed. Then, a series of tests, e.g., modified cyclic wetting and drying test, triaxial compression test and modified numerical simulation test for reservoir embankment red-bed mudstone, were conducted to verify the feasibility of the proposed models. In addition, grey system theory was originally used to evaluate the effects of the Weibull distribution parameters ( m and w ) and the confining stress on the peak stress. Finally, the proposed model was tentatively applied to the modification of the limit failure height model of the bedded rock slopes. The verification implies that the proposed model results are consistent with the testing results, especially in the simulation of compaction, elastic deformation and strain softening and in the prediction of peak strength. The results from grey system theory analysis indicate that the micro unit strength parameter ( w ) has the most obvious effect on the strength. Moreover, the modified method based on the damage evolution model for calculating the limit failure height of the bedded rock slopes is conservative.